Determinação da máxima concentração de suspensões de nanotubos de carbono em NMP e GPTMS - Toso, Guilherme Marino [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The solubility is a crucial point for the preparation of solutions and composite suspensions with electronic properties. This study presents an experimental apparatus construction for spectrophotometry measures dedicated to the determination of the maximum concentration of multi walled carbon nanotubes (MWCNT), in suspensions containing n-methyl- 2-pyrrolidone and 3-glycidoxypropyltrimethoxysilane as medium. Therefore, it was used a LED as a source of light, microscope slides for the fabrication of the cuvettes and an Ocean Optics HR4000 spectrophotometry for the optical absorbance determination of the suspensions. The results obtained with the developed instrument, were compared with the results obtained by a conventional apparatus, constituted by a spectrophotometry UV-Vis Varian Cary 50 and quartz cuvette. To determine the maximum concentration of MWCNT in the suspensions, the instrument was calibrated using diluted suspensions (with a concentration of 5 g/ml or lower). These data were analyzed with the Beer- Lamber Law establishing a relation between the suspension concentration and optical absorbance. To determine the maximum concentration of dispersion of the MWCNT in NMP and GPTMS, suspensions were prepared with a concentration of approximately 50 g/ml. These solutions were centrifuged during various periods (at 3000 rpm) to promove the precipitation of MWCNT agglomerate particles. The suspensions concentration were analyzed as a function of spin time and the data were analyzed with the Stokes' Law. In this way, it was determined the maximum concentration of MWCNT in suspensions without formation of agglomerates...

A solubilidade é um ponto crucial para a preparação de soluções e suspensões de compósitos com propriedades eletrônicas. Este estudo apresenta a construção de um aparato experimental para medidas de espectrofotometria dedicadas à determinação da máxima concentração de nanotubos de carbono de paredes múltiplas (MWCNT), em suspensões contendo n-metilpirrolidona e 3-glicidoxipropiltrimetoxisilano como meio. Para tanto, utilizou-se um LED como fonte de luz, lâminas de microscópio para a fabricação de cubetas e um espectrômetro Ocean Optics HR4000 para determinação da absorbância óptica das suspensões. Os resultados obtidos com o instrumento desenvolvido, foram comparados com resultados obtidos com um aparato convencional, constituído por um espectrofotô- metro UV-Vis Varian Cary 50 e cubeta de quartzo. Para determinação da máxima concentra ção de MWCNT nas suspensões foi feita a calibração do instrumento utilizando-se suspensões diluídas (com concentração de 5 g/ml ou inferior). Estes dados foram analisados com a Lei de Beer-Lambert estabelecendo-se uma relação entre concentração da suspensão e absorbância óptica. Para determinar a máxima concentração de dispersão de MWCNT em NMP e GPTMS, foram preparadas suspensões com concentração de aproximadamente 50 g/ml. Estas soluções foram centrifugadas durante diversos períodos (a 3000 rpm) para promover a precipitação das partículas de aglomerados de MWCNT. A concentração das suspensões foi avaliada como uma função do tempo de centrifugação e os dados foram analisados com a Lei de Stokes. Desta maneira, foi determinada a máxima concentração de MWCNT em suspensões sem formação de aglomerados...
Keywords: Nanotecnologia; Nanotubos de carbono; Solubilidade; Espectrofotometria